(Pyridin-4-yl)methyl N′-(3-phenylallylidene)hydrazinecarbodithioate. - Low, May Lee; S. A. Ravoof, Thahira Begum; Mohamed Tahir, Mohamed Ibrahim; Crouse, Karen Anne; Tiekink, Edward R. T. (International Union of Crystallography, 2013)
In the title compound, C16H15N3S2, the central C2N2S2 residue is planar (r.m.s. deviation = 0.045 Å) and the pyridyl and benzene rings are inclined and approximately coplanar to this plane, respectively [dihedral angles = 72.85 (9) and 10.73 (9)°], so that, overall, the molecule adopts an L-shape. The conformation about each of the N=C [1.290 (3) Å] and C=C [1.340 (3) Å] bonds is E. Supramolecular chains along [1-10] are stabilized by N—H(...)N(pyridine) hydrogen bonding and these are connected into a double layer that stacks along the c-axis direction by C—H(...)π(pyridine) interactions.